Implementasi Model Pembelajaran Problem Based Learning dalam Pembelajaran PAI di SD Pembangunan Laboratorium UNP - Aulia Azis; Rengga Satria (AS-SABIQUN, 2022)
The purpose of this study was to determine the implementation of the problem-based learning model from planning, implementation, and evaluation, as well as supporting and inhibiting factors. This research is qualitative research with a descriptive analysis technique. Data were obtained using interview, observation, and documentation techniques. The data analysis included three stages, namely the presentation of the data, and the drawing of conclusions. The results showed that at the UNP Laboratory Development Elementary School the implementation of the problem-based learning model was carried out by the 2013 curriculum. Planning is done with the teacher making lesson plans, and the implementation of learning is divided into three stages, namely preliminary activities, core activities, and closing activities. The core activities are carried out according to the syntax of the problem-based learning model. Evaluation includes three aspects, namely the cognitive, affective, and psychomotor domains. The inhibiting factor in the implementation of the problem-based learning model is learning time and students who feel bored, while the supporting factors are the supporting facilities and infrastructure at the UNP Laboratory Development Elementary School.